FACTORS CAUSING THE TRANSFER OF FOREST FUNCTION TO CORN FARMING LAND IN DOMPU REGENCY - Mita Parasti (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2021)
Abstract Nature is a component that plays an important role in human life. This big role cannot be separated from the provision of ecosystem services to fulfill needs in order to support life. These ecosystem services will not run properly if there is environmental damage. This environmental damage begins with the conversion of forest functions into corn agricultural land, humans only think about how to fulfill their desires without thinking about the impact it will have on nature and other humans. The purpose of this research is to find out the impact of land conversion which will change the function of the forest which should be the heart of earth's life into a corn farming field which will only benefit the parties concerned. Methods of collecting data using the interview method, direct observation of the field by looking at the existing conditions directly in the field. The results of this research show that there is a change in the function of forest land into corn agricultural land and changes the function of the area. Factors causing the conversion of forest functions are displacement, land use, economy and weak legislation. Key words : Environment, forest conversion, agriculture